Sexual Harassment During Internship: Experience of Indonesian student - Zulkarnain, Zulkarnain; Rahmawati, Patria; Kusuma, Bambang Jati; Kusumawati, Ratna Dewi; Amsal, Andi Yasir; Mahsun, Mahsun; Riklan, Riklan (Universitas Nusantara PGRI Kediri, 2025)
This study explores sexual harassment that occurs in students in an internship environment where students should have the opportunity to apply the knowledge gained while studying in higher education turns out to have the potential to be dangerous for sexual harassment. This study uses descriptive research using a self-report questionnaire. Sample and Background A practical sample consisting of 261 students (male and female) at the Balikpapan State Polytechnic. The results of this study show that female students become dominant victims with 4 dominant types of experiences such as, Sexual whistling/shouting, Demeaning because of gender, Offensive comments about appearance/body, uncomfortable gazes or unwanted invitations. Based on the results of this study, it is hoped that it can be an important consideration for universities in making regulations and efforts to prepare for the prevention of sexual harassment during internships in the industry in accordance with their respective fields before students leave for internships in the industry.